2023
DOI: 10.1111/lnc3.12497
|View full text |Cite
|
Sign up to set email alerts
|

Third language phonological acquisition: Understanding sound structure in a multilingual world

Abstract: The field of third language acquisition has gathered increased attention over the last three decades. However, phonological acquisition in an L3 is still relatively understudied within the field, despite there likely being over a billion people regularly using an L3 worldwide. In this paper, we review experimental and theoretical studies of sequential L3 acquisition to date and aim to give implications for future L3 phonological acquisition research, laying the groundwork for advances in this area. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Previous studies on L3 phonological acquisition have identified several factors that might contribute to CLI (see Wang and Nance, 2023 for an overview), such as (perceived) typological similarity (Llama et al, 2010;Cabrelli and Pichan, 2021), and experience with L3 (Cal and Sypiańska, 2020). Many studies argue in favor of property-by-property transfer in L3 phonology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on L3 phonological acquisition have identified several factors that might contribute to CLI (see Wang and Nance, 2023 for an overview), such as (perceived) typological similarity (Llama et al, 2010;Cabrelli and Pichan, 2021), and experience with L3 (Cal and Sypiańska, 2020). Many studies argue in favor of property-by-property transfer in L3 phonology.…”
Section: Introductionmentioning
confidence: 99%